ALEXITHYMIA PREDICTS COGNITIVE DEFICITS IN PATIENTS WITH IDIOPATHIC PARKINSON’S DISEASE - Gul, Amara; Yousaf, Javed (Journal of Ayub Medical College Abbottabad, 2019)
Background: In recent years, alexithymia has gained attention of medical researchers as a prognostic factor for serious health problems. The present study aimed to assess alexithymia as a determinant of cognitive decline in patients with Parkinson’s disease. Methods: Patients diagnosed with Parkinson’s disease (n=60) at Bahawal Victoria Hospital, Civil Hospital Bahawalpur and Nishter Hospital Multan during May 2016 until June 2017 participated in the study. Healthy individuals (n=60) took part in the study from local community as controls. Participants completed Bermond-Vorst Alexithymia Questionnaire and Montreal Cognitive Assessment. It was a cross sectional study design. Purposive sampling technique was used and data was analysed through multivariate analysis of variance and bivariate correlation. Results: Patients with Parkinson’s disease (177.96±8.93) showed higher attitudes of alexithymia as compared with healthy individuals (37.46±8.01), F (1,118)= 8216.52, p<0.001, Î·p2=.98. In contrast with healthy controls (28.60±0.58), patients with Parkinson’s disease (2.25±.95) were cognitively impaired F (1,118)=36424.38, p<0.001,Î·p2=.99. Alexithymia was a significant predictor of cognitive performance (R2=0.99, F (2, 119) = 5698.95, p<0.001). Conclusion: Alexithymia is a significant marker of cognitive decline in patients with Parkinson’s disease. Keywords: Parkinson’s disease; Cognition; Emotion; Alexithymia